THE EFFECT OF RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), AND CURRENT RATIO (CR) ON STOCK PRICE (A CASE STUDY AT PT. SIDO MUNCUL TBK IN 2016-2020) - Yuniarti, Rita; Hudana, Hamdan; Suciati, Elis; Roespinoedji, Djoko (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study was conducted based on the fluctuations in the stock price of PT. Sido Muncul Tbk. due to the corona pandemic, resulting in a decrease in sales that affect stock prices. This study aimed to investigate the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) on stock price at PT. Sido Muncul Tbk in 2016-2020. This study was conducted because there were still differences in research results between one study and another. Besides, it can be used to predict stock price fluctuations. The method used in this study was explanatory. The variables used in this study were Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), and stock price. The type of data used in this study was secondary data in the form of reports taken from the Annual report of PT. Sido Muncul Tbk in 2016-2020. The results showed that Return on Equity (ROE) and Debt to Equity Ratio (DER) had an effect on stock price, while Current Ratio (CR) had no effect on stock price.